Nomophobia and FOMO Syndrome: Emerging Psychosocial Risks in the Digital Workplace - Rubén, Rodríguez Elizalde (Disease and Health: Research Developments Vol. 7, 2025)
The digital era has revolutionized workplace dynamics, but it has also introduced new psychosocial risks that impact employees' mental health. Among these, technostress has gained prominence, manifesting in disorders such as Nomophobia (the irrational fear of being without a mobile device) and FOMO Syndrome (Fear of Missing Out). This study explores the intersection between these phenomena and occupational health, analyzing their psychological, behavioral, and organizational consequences. By reviewing recent literature and empirical data, the study highlights how excessive dependence on information and communication technologies (ICTs) contributes to anxiety, decreased productivity, and work-life imbalances. Furthermore, it discusses preventive strategies, including digital hygiene practices, cognitive-behavioral interventions, and corporate policies that foster healthier interactions with technology. As work environments become increasingly digital, understanding and mitigating the effects of Nomophobia and FOMO Syndrome is crucial for promoting sustainable mental well-being and optimizing workplace efficiency.